1990
DOI: 10.2355/isijinternational.30.854
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of remaining life of fossil power plant parts by means of a miniature creep rupture test.

Abstract: In order to validate a procedure for creep rupture tests using miniature specimens, a sampling technique and a method of making the miniature specimens were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Among the class of candidate materials preferred for such applications, 9-12% chromium (Cr) martensitic/ferritic steels are one of the primary choices of interest due to their excellent mechanical properties under such loading conditions (Hald, 2008;Klueh, 2005;Yoshizawa and Igarashi, 2007). Due to continuous optimization of their microstructure by metallurgical alloying over the last five decades, 9-12% Cr steels currently possess much improved structural properties that have helped USC power plants to reduce their specific carbon dioxide 0749-6419/$ -see front matter Published by Elsevier Ltd. http://dx.doi.org/10.1016/j.ijplas.2013.01.008 (CO 2 ) emissions by $30% (Armor and Viswanathan, 2005;Cerjak et al, 1999;Kadoya et al, 1990). Modified 9% Cr-1% molybdenum (Mo) -designated as grade P91 by the American Society for Testing and Materials (ASTM) -belongs to this class of advanced steels and is chosen extensively for elevated temperature components (Cohn et al, 2005;Kunz and Lukas, 2002;Sikka et al, 1983).…”
Section: Introductionmentioning
confidence: 97%
“…Among the class of candidate materials preferred for such applications, 9-12% chromium (Cr) martensitic/ferritic steels are one of the primary choices of interest due to their excellent mechanical properties under such loading conditions (Hald, 2008;Klueh, 2005;Yoshizawa and Igarashi, 2007). Due to continuous optimization of their microstructure by metallurgical alloying over the last five decades, 9-12% Cr steels currently possess much improved structural properties that have helped USC power plants to reduce their specific carbon dioxide 0749-6419/$ -see front matter Published by Elsevier Ltd. http://dx.doi.org/10.1016/j.ijplas.2013.01.008 (CO 2 ) emissions by $30% (Armor and Viswanathan, 2005;Cerjak et al, 1999;Kadoya et al, 1990). Modified 9% Cr-1% molybdenum (Mo) -designated as grade P91 by the American Society for Testing and Materials (ASTM) -belongs to this class of advanced steels and is chosen extensively for elevated temperature components (Cohn et al, 2005;Kunz and Lukas, 2002;Sikka et al, 1983).…”
Section: Introductionmentioning
confidence: 97%
“…Due to the elevated temperatures and stresses during testing, samples may require the use of an inert atmosphere within the test furnace, because oxidation effects are substantial on small specimens. Comparing the data with that in air it has shown that in an argon-rich environment the creep curves compare more favourably with those of conventional full size uniaxial specimens [9].…”
Section: Conventional Sub-size Creep Testmentioning
confidence: 72%
“…This is a tool that is used to relate the different geometries of all the individual non-standard small specimen tests to that of the full-size uniaxial test specimen. The gauge length 'l' used in conventional uniaxial creep tests and the sub-size uniaxial creep test constitutes the creep deformation as a fraction of the working gauge length, equation (9). The equivalent gauge length 'l e 'is a quantity that is derived from the geometry of the specimen in order to create an expression that models the creep strain in the unconventionally shaped small specimen tests to the conventionally shaped specimen…”
Section: Equivalent Gauge Lengthmentioning
confidence: 99%
“…A further refinement to the technique consists of using miniature specimens to minimize sample requirements. It has been demonstrated that miniature specimens (10 mm long, 3 mm diameter) tested in argon yield results representative of large specimens tested in air (Askins & Marchant 1988;Kadoya et al 1990).…”
Section: Creep Testsmentioning
confidence: 99%